Neurological Biomarker Profiles in Royal Canadian Air Force (RCAF) Pilots and Aircrew - Shawn G. Rhind; Maria Y. Shiu; Oshin Vartanian; Shamus Allen; Miriam Palmer; Joel Ramirez; Fuqiang Gao; Christopher J. M. Scott; Meissa F. Homes; Gary Gray; Sandra E. Black; Joan Saary (Brain Sciences)
Background/Objectives: Military aviators can be exposed to extreme physiological stressors, including decompression stress, G-forces, as well as intermittent hypoxia and/or hyperoxia, which may contribute to neurobiological dysfunction/damage. This study aimed to investigate the levels of neurological biomarkers in military aviators to assess the potential risk of long-term brain injury and neurodegeneration. Methods: This cross-sectional study involved 48 Canadian Armed Forces (CAF) aviators and 48 non-aviator CAF controls. Plasma samples were analyzed for biomarkers of glial activation (GFAP), axonal damage (NF-L, pNF-H), oxidative stress (PRDX-6), and neurodegeneration (T-tau), along with S100b, NSE, and UCHL-1. The biomarker concentrations were quantified using multiplexed immunoassays. Results: The aviators exhibited significantly elevated levels of GFAP, NF-L, PRDX-6, and T-tau compared to the CAF controls (p < 0.001), indicating increased glial activation, axonal injury, and oxidative stress. Trends toward higher levels of S100b, NSE, and UCHL-1 were observed but were not statistically significant. The elevated biomarker levels suggest cumulative brain damage, raising concerns about potential long-term neurological impairments. Conclusions: Military aviators are at increased risk for neurobiological injury, including glial and axonal damage, oxidative stress, and early neurodegeneration. These findings emphasize the importance of proactive monitoring and further research to understand the long-term impacts of high-altitude flight on brain health and to develop strategies for mitigating cognitive decline and neurodegenerative risks in this population.